A review of state of the art thermal diodes and their potential applications. (January 2021) - Wong, M.Y.; Tso, C.Y.; Ho, T.C.; Lee, H.H.
Highlights: Thermal diodes with various heat transfer mechanisms are summarized; Existing application studies of thermal diodes are discussed; Potential for further study and application directions of thermal diodes are presented. Abstract: Thermal management is an essential aspect of various applications, especially in the area of electronic miniaturization. Thermal diodes, which exhibit asymmetric heat transfer characteristics along an axial direction, are one of the vital components for use in thermal management systems. This review summarizes both theoretical and experimental studies of various types of thermal diodes introduced in recent years. The thermal diodes discussed in this review are classified based on their primary heat transfer mechanisms and the materials from which they are constructed. After gaining an understanding of the thermal rectification mechanisms of these thermal diodes, we also discuss several applications of thermal diodes, including solar power systems, caloric refrigeration systems, and thermal computing. Lastly, we present the application potential of the thermal diodes in several thermal systems that have not been investigated before, such as temperature controllers, micro-electronic cooling, space technologies, atomic clocks, and bio-technologies. Graphical Abstract: Image, graphical abstract